ATP6S1 elicits potent humoral responses associated with immune-mediated tumor destruction - Hodi, F. Stephen (The National Academy of Sciences, 2002)
An important goal of cancer immunology is the identification of antigens associated with tumor destruction. Vaccination with irradiated tumor cells engineered to secrete granulocyte/macrophage colony-stimulating factor (GM-CSF) generates potent, specific, and long-lasting antitumor immunity in multiple murine tumor models. A phase I clinical trial of this vaccination strategy in patients with advanced melanoma demonstrated the consistent induction of dense CD4(+) and CD8(+) T lymphocyte and plasma cell infiltrates in distant metastases, resulting in extensive tumor destruction, fibrosis, and edema. Antimelanoma antibody and cytotoxic T cell responses were associated with tumor cell death. To characterize the targets of these responses, we screened an autologous cDNA expression library prepared from a densely infiltrated metastasis with postvaccination sera from a long-term responding patient. High-titer IgG antibodies detected ATP6S1, a putative accessory unit of the vacuolar H(+)–ATPase complex. A longitudinal analysis of this patient revealed an association between the vaccine-induced increase in antibodies to ATP6S1 and tumor destruction. Three additional vaccinated melanoma patients and three metastatic non-small cell lung carcinoma patients vaccinated with autologous GM-CSF-secreting tumor cells similarly showed a correlation between humoral responses to ATP6S1 and tumor destruction. Moreover, a chronic myelogenous leukemia patient who experienced a complete remission after CD4(+) donor lymphocyte infusions also developed high-titer antibodies to ATP6S1. Lastly, vaccination with GM-CSF-secreting B16 melanoma cells stimulated high-titer antibodies to ATPS1 in a murine model. Taken together, these findings demonstrate that potent humoral responses to ATP6S1 are associated with immune-mediated destruction of diverse tumors.